Genetic variation in the major mitotic checkpoint genes associated with chromosomal aberrations in healthy humans. Issue 2 (1st October 2016) - Försti, Asta; Frank, Christoph; Smolkova, Bozena; Kazimirova, Alena; Barancokova, Magdalena; Vymetalkova, Veronika; Kroupa, Michal; Naccarati, Alessio; Vodickova, Ludmila; Buchancova, Janka; Dusinska, Maria; Musak, Ludovit; et al.
Highlights: Non-specific chromosomal aberrations (CAs) are detected in 1% of in vivo lymphocytes. Causes of CAs in population are not known but they may be related to risk of cancer. We genotyped 9 variants in mitotic checkpoint related genes on samples from healthy individuals. Gene pairs were significantly associated with CAs: PTTG1-ZWILCH and PTTG1-ZWINT. MAD2L1 and PTTG1 were the most common partners in any of the two-way interactions. Abstract: Non-specific chromosomal aberrations (CAs) are microscopically detected in about 1% of lymphocytes drawn from healthy persons. Causes of CAs in general population are not known but they may be related to risk of cancer. In view of the importance of the mitotic checkpoint machinery on maintaining chromosomal integrity we selected 9 variants in main checkpoint related genes (BUB1B, BUB3, MAD2L1, CENPF, ESPL1/separase, NEK2, PTTG1/securin, ZWILCH and ZWINT) for a genotyping study on samples from healthy individuals (N = 330 to 729) whose lymphocytes had an increased number of CAs compared to persons with a low number of CAs. Genetic variation in individual genes played a minor importance, consistent with the high conservation and selection pressure of the checkpoint system. However, gene pairs were significantly associated with CAs: PTTG1-ZWILCH and PTTG1-ZWINT. MAD2L1 and PTTG1 were the most common partners in any of the two-way interactions. The results suggest that interactions at the level of cohesin (PTTG1) and kinetochore function (ZWINT, ZWILCH and MAD2L1) contribute to the frequency of CAs, suggesting that gene variants at different checkpoint functions appeared to be required for the formation of CAs.